A Front-Row Seat to the Development of Grounded Theory - Kara L. Vander Linden; Odis Simmons (Grounded Theory Review: An International Journal, 2025)
Dr. Kara Vander Linden conducted this interview with Dr. Odis Simmons for the 2024 International Virtual Conference for Qualitative Research and Theory Methodologies.  In this interview, Dr. Odis Simmons described what it was like to be a student of Barney Glaser and Anselm Strauss at the University of California, San Francisco. He explains how his friendship with Glaser and Strauss gave him a front-row seat to the development of grounded theory. Dr. Simmons also shared information about a shift Barney Glaser made in the meaning and development of substantive grounded theory that has never been previously shared. This interview has been edited for clarity and readability.